Fronto-temporal Lobe Epilepsy Presenting as Intermittent Outburst of Anger: A Case Report from Eastern Nepal (Journal of Psychiatrists' Association of Nepal, 2021)
Episodes of rage and anger with violent outbursts are common manifestations of various psychiatric and behavioral disorders. Though rare, it can be a manifestation of fronto-temporal lobe epilepsy which is often misdiagnosed. Here we present a case of 20 years male having intermittent episodes of anger and violent outburst for three years who was later diagnosed as a case of fronto-temporal lobe epilepsy.